The determinents of accruals based earnings management :case of listed Moroccan companies - Hoummani, Sanae; Radi, Said (International Journal of Accounting and Economics Studies, 2017)
This article aims to identify the determinants of accruals based earning’s management in Moroccan listed companies. On one hand, it examines the relation between discretionary accruals as the measure of earning’s management and what literature documents as incentives to this practice, in particular, politico-contractual motivations, the avoidance of losses and earnings decreases and growth opportunities. On the other hand, it investigates whether corporate governance mechanisms may constrain management’s opportunistic behaviors. The empirical results provide evidence that managers manipulate earnings in the presence of losses and, that growing firms is more likely to engage in earning’s management. In terms of constraining factors, our findings indicate a negative relation between discretionary accruals and both institutional and concentrated ownership. Thus, we suggest that these shareholders play an effective role on monitoring managers.